Mummies and pyramids ebook A nonfiction companion to magic tree house #3: mummies in the morning. - Osborne, Mary Pope (Magic Tree House Fact Tracker, 2012)
The #1 bestselling chapter book series of all time celebrates 25 years with new covers and a new, easy-to-use numbering system! Getting the facts behind the fiction has never looked better.  Track the facts with Jack and Annie!!   When Jack and Annie got back from their adventure in  Magic Tree House #3: Mummies in the Morning,  they had lots of questions. Why did people make mummies? What was the mysterious writing on mummy cases? How did most ancient Egyptians spend their days? How were the pyramids built? Find out the answers to these questions and more as Jack and Annie track the facts. Filled with up-to-date information, photos, illustrations, and fun tidbits from Jack and Annie, the Magic Tree House Fact Trackers are the perfect way for kids to find out more about the topics they discovered in their favorite Magic Tree House adventures. And teachers can use Fact Trackers alongside their Magic Tree House fiction companions to meet common core text pairing needs.   Did you know that there’s a Magic Tree House book for every kid? Magic Tree House: Adventures with Jack and Annie, perfect for readers who are just beginning chapter books Merlin Missions: More challenging adventures for the experienced reader Super Edition: A longer and more dangerous adventure Fact Trackers: Nonfiction companions to your favorite Magic Tree House adventures Have more fun with Jack and Annie at MagicTreeHouse.com!